RESEARCH OF THE AERODYNAMIC PROCESS OF CARBON DUST REMOVAL FROM THE WORKING ZONE - Chencheva, О.; Lashko, Ye.; Rieznik, D.; Cheberyachko, Yu.; Petrenko, І. (Municipal economy of cities. Series: «Economy science», 2023)
The purpose of this work is research of the aerodynamic process of carbon dust removal from the working zone in order to create safe and harmless working conditions at the production site. As a result of the research, an aerodynamic calculation of a long air duct of uniform suction with tangential air intake was performed. The degree of twisting of the air flow inside the air duct, as well as the uniformity of air suction along the length of the long suction, were determined. A number of factors affecting the dust removal process have been established, such as suction torch long suction; coefficient of local suction resistance; forces of inertia and viscosity on the resistance of local suction. The dependence of the ratio of the width of the entrance hole to the diameter of the air duct on the local suction resistance, the dependence of the ratio of the areas of the entrance gap and the cross section of the transitional air duct on the local suction resistance, as well as the effect of the length of the entrance slot on the coefficient of local suction resistance were determined. The efficiency of suction of dust particles with an extended suction unit with tangential air entry has been proven. For a more accurate analysis of the distance at which an extended extractor with tangential air intake can be placed relative to the dust source, it is necessary to conduct a dispersed dust analysis. For effective capture of specific dust, calculations should be based on the size of the dust, which occupies a larger share in the distribution of fractions. The smaller the dust particle, the further the suction device can be located. To visualize the experimentally obtained results, simulation was performed in the FlowVision software in accordance with the mathematically calculated initial data. During the simulation of the movement of dusty air in an extended extractor with a tangential entry into the system, the occurrence of swirling of the air flow has been proven. Due to this formation, the largest fractions of dust will move along the walls of the air duct. This makes it possible to use extended extractors to remove coarse fractions of dust contained in polluted air, organizing the removal of air moving near the walls of the air duct.